Pengaruh latihan calf raises terhadap hasil shooting sepakbola pada SSB Putra Utama Desa Setia Darma - Rif’an Ahmad Albana; Ekowati Ekowati (Motion: Journal Research of Physical Education, 2023)
This study aims to determine the increase in shooting ability towards squat training at Ssb Putra Utama, Setia Darma Village. This study used experimental research methods through test and measurement instruments. The population in this study were 30 members of Ssb Putra Utama Setia Darma Village. The sample used in this study were 14 people using purposive sampling. Testing data analysis is done by normality test and homogeneity test which is tested by t test or t-tst. The results of this study show that the Calf Raises training method has a significant effect on improving ball shooting skills in soccer games at Ssb Putra Utama, with an average initial test score of 11 and an average final test score of 16 points, and an average increase of 4, 57 points. While the t-count value is 30.47 and is significant to alpha 5%.